Macroeconomic Variables on Indonesian Sharia Capital Market - Nugroho, Taufik; Rusydiana, Aam S. (Shirkah: Journal of Economics and Business, 2018)
This article emphasizes to analyze the effect of macroeconomic variables on sharia capital market in Indonesia by using Vector Error Correlation Model (VECM) approach method. The variables used are world oil price, Industry Production Index (IPI) Currency Exchange Rate to Dollar and Consumer Price Index (CPI) in Indonesia. The research show that in the Indonesian Stock Sharia Index (ISSI) model, the VECM in the ISSI model can explain in the short term the IPI variable, world oil price, rupiah to dollar, DJIA and CPI does not affect to ISSI variable. While in the long term, world oil prices are positive climate and Dow Jones Industrial Average (DJIA) variables negatively affect ISSI. In addition, FEVD test the world oil price has more dominant contribution than other variable 6.02%. Keywords: sharia capital market, macroeconomics, VECM, ISSI